PENGARUH PEER-TO-PEER LENDING DAN FINANCIAL TECHNOLOGY TERHADAP KESEJAHTERAAN MASYARAKAT: PERAN PENINGKATAN PENDAPATAN UMKM SEBAGAI INTERVENING - Eka Sariningsih; Septi Mutia; Isnia Susmita; Kausar Maha Prama (ITB AAS Indonesia Surakarta, 2026)
This study examines the influence of Peer-to-Peer (P2P) lending, financial technology (fintech), financial management, and production costs on community welfare, with an increase in MSME income as an intervening variable. SMEs play a crucial role in economic growth but are often hindered by limited access to capital and suboptimal financial management. P2P lending and fintech serve as alternative funding solutions that are easier and faster, potentially driving an increase in SMEs income. The research method employs a quantitative approach with path analysis. Primary data is collected through questionnaires distributed to SMEs actors in Gedong Tataan District. The findings reveal that P2P lending, fintech, and financial management both partially and simultaneously have a positive and significant effect on the increase in MSME income. The increase in MSME income further has a positive and significant effect. Keywords: Peer-To-Peer Lending, Financial Technology, community welfare, income improvement, SME